Making the law of the jungle: the reform of forest legislation in Bolivia, Cameroon, and Indonesia - Silva, E.; Kaimowitz, D.; Bojanic, A.; Ekoko, F.; Manurung, T.; Pavez, I. (2002)
The debates over sustainable development put environmental issues squarely on the policy agendas of nations around the world. Throughout, the fate of the forest occupied center stage, and domestic and international pressure induced many developing nations to reform their forest policy, which frequently culminated in new forest legislation. Yet the process that generated those new forest laws has not received much attention and a number of questions remain unanswered. What factors determine whether governments reform forest laws in the first place? What conditions influence the direction of reform? What role does expert advice play in the process? This paper applies a political economy framework that focuses on the interplay between international structure, domestic structure and ideas to answer those questions. It argues that this approach offers the best tools for analyzing the actors and interests involved in the policy process and their power resources. Among the most significant findings are that the World Bank is not as influential in the end as is commonly perceived. Moreover, in democratic developing countries organizations that focus almost exclusively on cultivating their relationship with state ministries to influence forest policy reform usually see their efforts flounder because the legislature, especially legislative committees, is a more significant policy making arena than had been considered here before.